Dynamic voltage stability of unbalanced distribution system with high penetration of single‐phase PV units. Issue 17 (15th April 2019) - Islam, Monirul; Mithulananthan, Nadarajah; Hossain, Jahangir; Shah, Rakibuzzaman
Abstract : Dynamic voltage instability (DVI) issues are the primary concern in low‐voltage distribution network (DN) due to growing integration of low‐inertia compressor motor loads such as air‐conditioner and refrigerator. The concern of DVI is likely to increase owing to high penetration of rooftop type single‐phase photovoltaic (PV) units in DN. On the other hand, DNs are inherently unbalanced as a result of load and line characteristics along with unbalanced PV penetration. This paper examines the impact of imbalance on the dynamic voltage stability (DVS) in DN and provides solutions to mitigate any adverse effects. Dynamic models of the single‐phase PV units are developed and utilised in the paper. The degree of unbalanced is defined first, and then its impact on the DVS is investigated. From the investigation, it is observed that degree of instability is increased with the increment of imbalance. The paper has also proposed a mitigation strategy i.e. reactive power injection by PV inverter. Case studies are conducted on modified IEEE 4 bus system which represents a low‐voltage DN. Results reveal that reactive power injection by PV inverter can improve the DVS by mitigating the impact of unbalance.